Portfolio risk and return between energy and non-energy stocks - Neeraj Nautiyal; Abdel Razzaq Alrababa'a; Mobeen Ur Rehman; Xuan Vinh Vo; Mamdouh Abdulaziz Saleh Al-Faryan (Heliyon, 2024)
This paper aims to examine the potential for portfolio returns by adding together conventional and energy stocks with varying proportions. We examine the risk and return characteristics of a portfolio comprising energy and non-energy stocks from twenty countries. The period for daily data ranges from 2nd July 1999 to 2nd July 2021. We use multiscale Sharpe and VaR ratios to examine the risk and returns behaviour of a portfolio with varying composition between energy and non-energy stocks across different investment periods. Our results highlight optimal returns for the equally weighted portfolio during normal and crisis periods except COVID-19 during which more proportion of conventional stocks is preferred. Risk estimates advocate an equally weighted portfolio for all periods however risk varies with the holding period. These results carry useful investment implications during short- and long-run holdings of conventional and energy stocks in a portfolio.